Doch kein NEPP? Struktur und Wettbewerbswirkungen des revidierten NAP II. - Matschoss, Patrick (Dt. Fachverl., 2008)
Nachdem der ursprünglich nach Brüssel notifizierte NAP II-Entwurf noch reichlich Ähnlichkeit mit dem NAP I hatte, wurde die jetzt verabschiedete Fassung signifikanten Änderungen unterzogen. Mit dem Einstieg in die Versteigerung, dem reduzierten Budget und einer revidierten Neuanlagenregelung enthält der NAP II jetzt drei wichtige Verbesserungen, von denen zwei auf die Ablehnung des NAP II-Entwurfs durch die Europäische Kommission zurückzuführen sind. Insgesamt hat die Entwicklung seit dem Frühjahr 2006 viele Beobachter und Akteure überrascht. Mit dem brennstoffspezifischen benchmark bleibt jedoch eine signifikante Schwäche des NAP erhalten.

The paper describes the structure and competitiveness effects of the German National Allocation Plan (NAP) for the second trading period within the European Emissions Trading Scheme. Grandfathering constitutes a significant subsidy. This has led to heavy rent seeking by the regulated entities as well as to the introduction of additional policy goals by the government. As a result, NAP I was highly complex and weak environmental target. Whereas the initial versions of the NAP II suggested a continuation of this policy, the version that was finally adopted resembles three major innovations: the introduction of partial auctioning, a more stringent emission target and a revised regulation on new entrants. The latter two where due to the European Commission's rejection of the early NAP II whereas the introduction of auctioning may be attributed to a change in the public perception on the opportunity costs of grandfathered allowances. Taken together, the development since spring 2006 has taken many stakeholders and observers by surprise. However, the split benchmark, granting a higher allocation to coal-based electricity generation, remains a ignificant weakness.
Keywords: Umweltschutz; Umweltpolitik; Klima; Energiepolitik; Energieproduktion; Kohlendioxid; Emission; Industrie; Energiewirtschaft; Kraftwerk; Neubau; Klimaschutz; Emissionshandel; EG-Richtlinie; Treibhausgas; Budget